Kesetaraan Gender Dalam Al-Qur’an: Kritik Terhadap Pemikiran Panji Gumilang Atas Penafsiran Q.S Al-Ahzab: 35 - Zayyadi, Ach; Wildania Sholeha, Fina (Universitas Yudharta Pasuruan, 2023)
An interpretation will be influenced by the mufassir, where the character of the mufassir is also influenced by his life background and education. If a mufassir has brought a certain understanding, then a mufassir like this will never be able to follow the guidance of the Al-Qur'an. In fact, he will try to force the Koran to follow his understanding even if it is wrong. The most important thing for the interpreter is to adhere firmly to the rules of interpretation so that they are in line with the message and objectives of the Al-Qur'an. This research examines the issue of gender equality in prayer prayers with a focus on the interpretation of Panji Gumilang regarding the equalization of prayer prayers between men and women. This research aims to understand the concept of gender equality in the Al-Quran and criticize the interpretation of Panji Gumilang from the perspective of Munir's interpretation. The research method used is qualitative, by collecting data from Al-Quran commentary books, related books, opinions of commentators, and other relevant sources. Data analysis was carried out using the tafsir tahlili method which explores aspects of the verses of the Al-Qur'an and explains their meaning according to the views of the interpreter who interprets the verse. It is hoped that this research will provide deeper insight into gender equality in the context of prayers based on the Al-Qur'an.